1989
DOI: 10.1002/acp.2350030305
|View full text |Cite
|
Sign up to set email alerts
|

Using statistical risk information to assess oral contraceptive safety

Abstract: The effect of variations in the presentation of oral contraceptive risk information on perceived safety was investigated. Four tests of the hypothesis that consumers focus on the absolute value of the numbers presented when assessing risk probabilities were performed with the following results: (1) when base rates are given, risks are perceived as less likely than when base rates are not given; (2) risks seem smaller when the information provided focuses on the number that will not die than when the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 11 publications
2
47
0
2
Order By: Relevance
“…Th at is, a 10% risk should be interpreted as a 10% risk, regardless of whether it is presented as a percentage or an odds ratio or whether it is presented numerically or pictorially. Unfortunately, empirical tests of probability-based communications have typically failed to support this premise [e.g., (31,32)]. People have diffi culty recalling probability information accurately [e.g., (33,34)], they make errors when asked to transform percentages into proportions or vice versa (e.g., Lipkus I: unpublished data [numeracy survey], 1998), and they confuse information about the frequency of a event with its rate of occurrence [e.g., (35)].…”
Section: Impact Of Probability-based Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Th at is, a 10% risk should be interpreted as a 10% risk, regardless of whether it is presented as a percentage or an odds ratio or whether it is presented numerically or pictorially. Unfortunately, empirical tests of probability-based communications have typically failed to support this premise [e.g., (31,32)]. People have diffi culty recalling probability information accurately [e.g., (33,34)], they make errors when asked to transform percentages into proportions or vice versa (e.g., Lipkus I: unpublished data [numeracy survey], 1998), and they confuse information about the frequency of a event with its rate of occurrence [e.g., (35)].…”
Section: Impact Of Probability-based Approachesmentioning
confidence: 99%
“…Moreover, Yamagishi (42) found that people rated a health problem as riskier when they were informed that it kills 1286 of 10000 people (12.86%) compared with 24.14 of 100 people (24.14%). It would appear that people fail to consider the relevant sample size when processing information regarding the number of people who have developed or died from a health problem [but see (31)]. …”
Section: Impact Of Probability-based Approachesmentioning
confidence: 99%
“…Subjects tend to pay attention to actual magnitude information, irrespective of the unit of measurement. Halpern et al (1989) demonstrate that subjects perceived "4.15 times greater" to be equivalent to "415% times greater," though the former is actually equivalent to "315% times greater." Further, even though subjects perceive "4.15 times" and "415%" to be equivalent, they judge 415% as a greater risk of death than 4.15 times, based purely on the magnitude of the numbers presented.…”
Section: Frequency Wording Eflectsmentioning
confidence: 95%
“…For example, respondents have been shown to ignore the format in which numerical information is provided and make judgments based on the absolute magnitudes of the number provided (Halpern, Blackman and Salzman 1989). This led to people perceiving "100% greater" to mean "twice" as large, and "200% greater" to also mean "twice" as large!…”
Section: Availability Of Alternative Sources Of Informationmentioning
confidence: 99%
“…This led to people perceiving "100% greater" to mean "twice" as large, and "200% greater" to also mean "twice" as large! Halpern et al (1989) also showed that "4.15 times greater" was perceived to be equivalent to "415% times greater" rather than the normatively correct "315% times greater." Interestingly, presenting information as a percentage or as number of times (i.e., actual frequency), also affected risk perceptions: though people perceived "4.15 times" to be the same as "415%" they judged 415% to be a greater risk of death than 4.15 times.…”
mentioning
confidence: 99%